Respuesta :

Answer:

The first one?

Step-by-step explanation:

sorry if im wrong

Answer:

Statement Two: The y-intercept of Function A is less than the y-intercept of Function B

Step-by-step explanation:

The y-intercept of Function A is -1

To calculate the y-intercept of Function B we first need to determine the slope.

The formula for slope is [tex]\frac{y_{2}-y_{1} }{x_{2} -x_{1} }[/tex]   [tex]\frac{4-2}{9-3} =\frac{2}{6} =\frac{1}{3}[/tex]

Now that we have the slope (1/3 x) we can find the y-intercept

[tex]b=y-mx[/tex]

[tex]b=0-(\frac{1}{3})(-3)[/tex]

[tex]b=1[/tex]

1 > -1, so Statement Two is true

plz mark me brainliest. :)